THE CULTURAL AND CREATIVE FORMATION OF YOUTH IN THE 21ST CENTURY AS A PROBLEM - Pardayev Sobit Abdivali o‘g‘li; Mirzayeva Dilfuza Bahodir qizi (Ustozlar uchun, 2025)
Abstract: This article reveals the significance of the types of creative and cultural activities, the social and pedagogical content of the concept of creative and cultural activities.